A review on resveratrol-loaded liposome and its characterisation / Shafyrna Zulkeffleey, Wan Azman Wan Ismail and Kashif Shakeel - Zulkeffleey, Shafyrna; Wan Ismail, Wan Azman; Shakeel, Kashif (Faculty of Pharmacy, 2021)
Resveratrol (3,5,4′-trihydroxystilbene) is a stilbene-type natural polyphenol found in a variety of plant species, including grapes, berries, peanuts, and red wine. Many studies have demonstrated that resveratrol as a nutraceutical supplement, exhibits numerous pharmacological properties such as antioxidant, anti-inflammatory, cardio-protective, neuroprotective, chemo-preventive, and anti-aging. Despite its health-beneficial effects, resveratrol has extremely low water solubility, high absorption, and rapid metabolism that consequently reduces its oral bioavailability. Hence, there have been a growing interest in a liposome as a carrier to optimise its limitations over the past few years. The purpose of this research is to review the potential of liposomes as a suitable carrier to optimise resveratrol limitations and evaluate characteristics pertaining to resveratrol-loaded liposomes based on the articles that have been published. The method for literature search is based on three search strategies: 1) database searches (PubMed free search engine from the United States National Library of Medicine and the Science Direct browser from Elsevier); 2) web-based searches (Google Scholar); and 3) citation searches. The selected articles were restricted from 2016 to 2021 in English, where 107 articles were chosen. This review summarises the findings of liposomes incorporating resveratrol in recently published articles and highlights the potential of liposomes in improving resveratrol limitations, consequently, promoting its pharmacological effects. Therefore, characteristics such as particle size, morphology, in-vitro drug release, entrapment efficiency, and stability test, were also evaluated. Resveratrol-loaded liposomes provide excellent solubility, stability, improved drug release, and high entrapment efficiency; thus, it may increase oral bioavailability and efficacy, both of which would promote its pharmacological effects.